2016
DOI: 10.1177/1077695816666077
|View full text |Cite
|
Sign up to set email alerts
|

Designing Journalism Capstone Units That Demonstrate Student Skills

Abstract: There are considerable differences in the structure, content, and delivery of tertiary journalism degrees in Australia as identified in a 2014 Office for Learning and Teaching (OLT) Innovation and Development Project report on graduate qualities and journalism curriculum renewal. To address this situation, the author argues for journalism capstone units, designed by both journalism educators and news editors, to include a series of agreed criteria and standards to guide journalism educators, and for journalism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…For instance, they can utilize audiovisual teaching for self-learning, i.e., using electronic equipment of films, video files, and recorders for delivering teaching content. It is suggested that the hospitality industry, in addition to stressing employees’ educational training, should list constant expenses for purchasing educational training-related equipment to promote educational effectiveness ( Cullen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they can utilize audiovisual teaching for self-learning, i.e., using electronic equipment of films, video files, and recorders for delivering teaching content. It is suggested that the hospitality industry, in addition to stressing employees’ educational training, should list constant expenses for purchasing educational training-related equipment to promote educational effectiveness ( Cullen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interviews are a common way for researchers to better understand both journalism and journalism education, including Jaakkola (2018) using interviews to study pedagogical newsrooms, Ferrucci (2018) using the approach to understand journalist’s views of journalism programs, and Cullen (2016) using the method to understand how journalism capstones demonstrate student skills. Wenzel (2020) used interviews to gather data from both community members and journalists, asking journalists about their outlets, challenges they face, and how they conceive of their audiences.…”
Section: Research Questions Participant Population and Methodsmentioning
confidence: 99%
“…While research on student-run magazines is slim, the literature on student journalism education suggests that student media involvement can facilitate a seamless college to career transition. Surveyed journalism capstone faculty have focused on teaching newswriting, social media savviness, and journalism ethics (Cullen, 2016). Operating models differ on how much they mimic professional outlets depending on their editorial and financial independence from the university-a decision faculty must grapple with (Bockino, 2018).…”
Section: Student Journalism As Job Trainingmentioning
confidence: 99%